Detection and characterization of a ring chromosome in the fission yeast Schizosaccharomyces pombe. - Fan, J B (1992)
NotI and SfiI genomic restriction maps were used to detect and characterize a ring chromosome II in a Schizosaccharomyces pombe strain with a meiotic defect on chromosome II. The ring chromosome was formed by an intrachromosomal fusion near, or at, the very ends of chromosome II.